2018
DOI: 10.4103/ijmbs.ijmbs_8_18
|View full text |Cite
|
Sign up to set email alerts
|

Use of donors at age extremes for simultaneous pancreas-kidney transplant

Abstract: Type 1 diabetes mellitus (T1DM) is a major cause of morbidity and mortality in the United States and accounts for about 245 billion annual health-care costs. [1][2][3][4] There are 1.25 million Americans are living with T1DM, 85% of who are adults, with 40, 000 new diagnoses each year, and an estimated 5 million people with T1DM in the U. S. by 2050. [3][4][5][6][7] Simultaneous pancreas-kidney transplant (SPKT) is a well-established treatment for patients with T1DM complicated by end-stage renal disease. [8][… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Although the age threshold by which older and reference-aged pancreas donors are commonly defined ranges 45À50 years (less commonly defined in pancreas transplant recipients), other studies have analysed a range of donor and recipient age thresholds for associations with solid pancreas transplant outcomes, which did not meet inclusion criteria for our review. Among such studies were eight studies comparing outcomes in groups differentiated by recipient upper age limits ranging 45À60 years, 9,34,[38][39][40][41][42][43] six studies comparing outcomes in groups differentiated by donor upper age limits ranging 40À50 years 7,[44][45][46][47][48] and two studies comparing outcomes in donor-recipient age-matched groups. 49,50 Of these, seven of eight studies comparing outcomes by recipient age showed no significant difference in primary outcomes between groups (Supporting Information Table S5).…”
Section: Very Low Admentioning
confidence: 99%
“…Although the age threshold by which older and reference-aged pancreas donors are commonly defined ranges 45À50 years (less commonly defined in pancreas transplant recipients), other studies have analysed a range of donor and recipient age thresholds for associations with solid pancreas transplant outcomes, which did not meet inclusion criteria for our review. Among such studies were eight studies comparing outcomes in groups differentiated by recipient upper age limits ranging 45À60 years, 9,34,[38][39][40][41][42][43] six studies comparing outcomes in groups differentiated by donor upper age limits ranging 40À50 years 7,[44][45][46][47][48] and two studies comparing outcomes in donor-recipient age-matched groups. 49,50 Of these, seven of eight studies comparing outcomes by recipient age showed no significant difference in primary outcomes between groups (Supporting Information Table S5).…”
Section: Very Low Admentioning
confidence: 99%